2020
DOI: 10.1051/0004-6361/201936974
|View full text |Cite
|
Sign up to set email alerts
|

From stellar coronae to gyrochronology: A theoretical and observational exploration

Abstract: Context. Stellar spin-down is the result of a complex process involving rotation, dynamo, wind and magnetism. Multi-wavelength surveys of solar-like stars have revealed the likely existence of relationships between their rotation, X-ray luminosity, mass-losses and magnetism. Those impose strong constraints on the corona and wind of cool stars. Aims. We aim to provide power-law prescriptions of the mass-loss of stars, of their magnetic field, and of their base coronal density and temperature that are compatible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 89 publications
(193 reference statements)
1
27
0
Order By: Relevance
“…Such a modeling requires knowledge of the temperature T c and density n c at the base of the wind. For consistency with the observational constraints on stellar rotation, wind, and magnetism, we rely on the Ahuir et al (2020) prescriptions for those quantities. More precisely, as the stellar magnetic field measured from Zeeman broadening and Zeeman-Doppler imaging (see Montesinos & Jordan 1993;Vidotto et al 2014;See et al 2017) have only exhibited linear or super-linear dependencies between the large-scale magnetic field and the Rossby number, we consider for the sake of simplicity the following scaling law to assess the magnetic field at the stellar surface B (Ahuir et al 2020):…”
Section: Magnetic Star-planet Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a modeling requires knowledge of the temperature T c and density n c at the base of the wind. For consistency with the observational constraints on stellar rotation, wind, and magnetism, we rely on the Ahuir et al (2020) prescriptions for those quantities. More precisely, as the stellar magnetic field measured from Zeeman broadening and Zeeman-Doppler imaging (see Montesinos & Jordan 1993;Vidotto et al 2014;See et al 2017) have only exhibited linear or super-linear dependencies between the large-scale magnetic field and the Rossby number, we consider for the sake of simplicity the following scaling law to assess the magnetic field at the stellar surface B (Ahuir et al 2020):…”
Section: Magnetic Star-planet Interactionsmentioning
confidence: 99%
“…( 19)) can affect the relative importance of the magnetic torque in our model. To illustrate this we consider the alternative prescription proposed by Ahuir et al (2020), which shows the steepest Rossby number dependency:…”
Section: Influence Of Stellar Magnetism On Planet Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest uncertainty lies here in the lack of knowledge of the key stellar properties (rotation period, magnetic field) in the sample. For this review I revisited the updated ensemble of Kepler-observed exosystems while using the wind-modelling strategy developed by Ahuir et al (2020). This strategy can be applied for the stars with a detected rotational period (McQuillan et al 2014): a stellar Rossby number can then be estimated based on the scaling law derived from 3D numerical simulation by Brun et al (2017).…”
Section: Stellar Dipole Stellar Quadrupolementioning
confidence: 99%